Investigation of Korean female golfers` success factors on the LPGA Tour from 1998 to 2007 - Bae, W. Y. (The Sport Journal, 2012)
Se Ri Pak is arguably the most famous Korean name ever to play on the LPGA Tour. Ten years after Pak`s debut in 1998, 42 Korean players are now playing on the LPGA Tour. This international phenomenon over the past decade has produced a lot of Korean players and many Korean victories. Nineteen-Koreans have won 64 LPGA Tour events over the past decade. Therefore, the purpose of this study is to analyze the reasons why Korean female golfers have been successful in securing such a dominant position on the LPGA Tour. The survey used in this study was distributed to Korean players who participated in a professional golf event (State Farm Classic Tournament). The results of this study revealed that hard practice, certain goal, and family support were selected as the most important factors to be success on the LPGA Tour by Korean players.